LBO-1.3 Syphilis infection and associated behaviours among transgender women, Chicago 2010. (10th July 2011) - Gratzer, B; Hotton, A; Pineda, M; Pohl, D; Martinez, L
Abstract : Background: Transgender women are an underserved and understudied population with unique medical and behavioural risk profiles. High rates of STIs and HIV in this population have been reported, although accurately quantifying STI rates and associated risks is difficult because of limitations in measurement of gender identity, lack of standardised reporting measures, and conflation between Men who Have Sex with Men (MSM) and transgender identities. In 2009 we reported a substantial increase in syphilis among transgender women at our clinic (from two cases in 4 years to ten cases in 1 year); in 2010 we identified 20 new cases, another substantial increase. We sought to describe morbidity and behavioural characteristics of these cases to better understand trends among this population. Methods: Data were gathered using clinic-based sentinel surveillance systems and through abstraction of Interview Records completed upon DIS interview. Results: Transgender women represented an increasing proportion of total syphilis cases identified from 2009 (3.7% or 10/269) to 2010 (6.4% or 20/313). The 20 cases identified in 2010 were among 19 transgender women; one client was re-infected. Of these, 2 (10%) were primary, 12 (60%) were secondary, 5 (25%) were early latent, and 1 (5%) was latent of unknown duration syphilis. The mean age increased slightly from 21.4 years (range 19–24) in 2009 to 24.9 years (range 19–41) in 2010. Reported race/ethnicity included: 13 (65%) non-Hispanic black, 3 (15%) Hispanic, 2 (10%) non-Hispanic white, 1 (5%) Asian/Pacific Islander and 1 (5%) American Indian/Alaskan Native. HIV co-infection was similar to rates observed in Men who Have Sex with Men (MSM) populations (60%); 25% of HIV-positive clients had been diagnosed in the prior year. Forty-five per cent had a history of STI (non-HIV). High rates of transient housing (30%), unemployment (55%), incarceration (25%), and transactional sex (40%) in the prior 12 months were reported. Median number of sex partners in the past year was 10 (range 0–60). No common sex partners were named during case investigation interviews during 2009 or 2010. Conclusions: Increases in syphilis among transgender women in Chicago highlight a need for enhanced screening and targeted prevention messages for this population. High levels of risk and HIV co-infection reflect potential for ongoing transmission of both HIV and other STIs.